Risk of microalbuminuria and progression to macroalbuminuria in a cohort with childhood onset type 1 diabetes: prospective observational study. Issue 7646 (18th March 2008) - Amin, Rakesh; Widmer, Barry; Prevost, A Toby; Schwarze, Phillip; Cooper, Jason; Edge, Julie; Marcovecchio, Loredana; Neil, Andrew; Dalton, R Neil; Dunger, David B
Abstract : Objectives To describe independent predictors for the development of microalbuminuria and progression to macroalbuminuria in those with childhood onset type 1 diabetes. Design Prospective observational study with follow-up for 9.8 (SD 3.8) years. Setting Oxford regional prospective study. Participants 527 participants with a diagnosis of type 1 diabetes at mean age 8.8 (SD 4.0) years. Main outcome measures Annual measurement of glycated haemoglobin (HbA1c ) and assessment of urinary albumin:creatinine ratio. Results Cumulative prevalence of microalbuminuria was 25.7% (95% confidence interval 21.3% to 30.1%) after 10 years of diabetes and 50.7% (40.5% to 60.9%) after 19 years of diabetes and 5182 patient years of follow-up. The only modifiable adjusted predictor for microalbuminuria was high HbA1c concentrations (hazard ratio per 1% rise in HbA1c 1.39, 1.27 to 1.52). Blood pressure and history of smoking were not predictors. Microalbuminuria was persistent in 48% of patients. Cumulative prevalence of progression from microalbuminuria to macroalbuminuria was 13.9% (12.9% to 14.9%); progression occurred at a mean age of 18.5 (5.8) years. Although the sample size was small, modifiable predictors of macroalbuminuria were higher HbA1c levels and both persistent and intermittent microalbuminuria (hazard ratios 1.42 (1.22 to 1.78), 27.72 (7.99 to 96.12), and 8.76 (2.44 to 31.44), respectively). Conclusion In childhood onset type 1 diabetes, the only modifiable predictors were poor glycaemic control for the development of microalbuminuria and poor control and microalbuminuria (both persistent and intermittent) for progression to macroalbuminuria. Risk for macroalbuminuria is similar to that observed in cohorts with adult onset disease but as it occurs in young adult life early intervention in normotensive adolescents might be needed to improve prognosis.